The mRNA and miRNA profiles of goat bronchial epithelial cells stimulated by Pasteurella multocida strains of serotype A and D - An, Qi; Chen, Si; Zhang, Luyin; Zhang, Zhenxing; Cheng, Yiwen; Wu, Haotian; Liu, Ang; Chen, Zhen; Li, Bin; Chen, Jie; Zheng, Yiying; Man, Churiga; et al. (PeerJ, 2022)
Pasteurella multocida (P. multocida) is a zoonotic bacterium that predominantly colonizes the respiratory tract and lungs of a variety of farmed and wild animals, and causes severe respiratory disease. To investigate the characteristics of the host immune response induced by P. multocida strains of serotype A and D, high-throughput mRNA-Seq and miRNA-Seq were performed to analyze the changes in goat bronchial epithelial cells stimulated by these two serotypes of P. multocida for 4 h. Quantitative RT-PCR was used to validate the randomly selected genes and miRNAs. The results revealed 204 and 117 differentially expressed mRNAs (|log2(Fold-change)| ≥ 1, p-value < 0.05) in the P. multocida serotype A and D stimulated groups, respectively. Meanwhile, the number of differentially expressed miRNAs (|log2(Fold-change)| > 0.1, p-value < 0.05) were 269 and 290, respectively. GO and KEGG enrichment analyses revealed 13 GO terms (p-value < 0.05) and four KEGG pathways (p-value < 0.05) associated with immunity. In the serotype A-stimulated group, the immune-related pathways were the GABAergic synapse and Toll-like receptor signaling pathways, while in the serotype D-stimulated group, the immune-related pathways were the phagosome and B cell receptor signaling pathways. Based on the predicted results of TargetScan and miRanda, the differentially expressed mRNA–miRNA network of immune-related GO terms and KEGG pathways was constructed. According to the cell morphological changes and the significant immune-related KEGG pathways, it was speculated that the P. multocida serotype D strain-stimulated goat bronchial epithelial cells may induce a cellular immune response earlier than serotype A-stimulated cells. Our study provides valuable insight into the host immune response mechanism induced by P. multocida strains of serotype A and D.
Keywords: mRNA-Seq; miRNA-Seq; Pasteurella multocida; Goat bronchial epithelial cells; Immune response